Impact of perioperative period on disease-free survival among carcinoma ovary patients treated with the interval cyto-reductive surgery at a tertiary cancer centre in Kerala, India: a retrospective study - Dharmarajan, Adarsh; V., Vinin N.; Nair, Chandran K.; Badesara, Sanjay; Selvaraj, Kalaiselvi; Rathi, Priya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Global incidence of ovarian malignancies is 300,000 as per GLOBOCAN 2018. The treatment protocol for advanced ovarian malignancies (stage IIIc and stage IV) includes neo-adjuvant chemotherapy and surgery followed by adjuvant chemotherapy. Aims of the study was to determine the effect of duration of chemo interruption on disease free survival of ovarian malignancies treated by interval cytoreduction followed by surgery. Methods: A total 48 patients were studied for events such as recurrence, death, patient’s status on last follow up, peri-operative period between 3rd cycle of chemo therapy and 4th cycle of chemo therapy. Based on the median duration of peri operative period patients was classified as early or delayed receivers of adjuvant chemo therapy. Difference in duration of over-all survival and disease-free survival was analysed through Kaplan Meier survival analysis using log-rank test. Hazard ratio adjusted for background characteristics such as staging, performance status, grade of tumour were analysed using cox proportional hazard model. Results: The two peri operative period categories based on mean value (85 days) didn’t show any significant association to disease free interval (minimum-21days, maximum-146 days, Hr = 1.3, p-value = 0.52). Other established factors like stage, extent of resection, response to chemotherapy, also didn’t show any significant association. Serum marker level showed a significant negative correlation with disease free survival (minimum-9 days, maximum-30659, p-value =.04, Hr = 3.19). Conclusions: The study could not establish any correlation between peri operative period and median disease-free survival. The small sample size is a limiting factor, well controlled randomized trials may needed for further clarification.